1993
DOI: 10.1016/s0010-9452(13)80208-0
|View full text |Cite
|
Sign up to set email alerts
|

Laterality in Cats: Paw Preference And Performance in a Visuomotor Activity

Abstract: Laterality in paw use was investigated over a period of 6 years in 44 domestic cats trained to perform a reaching movement toward a moving spot of light. Both paw preference and paw performance were recorded. At a 50 percent criterion, no significant paw preference was found at the level of the group. When a 90 percent criterion was considered, 23 subjects had a significant preference for one paw. Among these strongly lateralized animals, there were more left- (N = 17) than right-pawed (N = 6) cats. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…Hence, the left eye of chicks with lateralization is consistently faster at detecting a novel stimulus. This result is rather similar to results of Fabre- Thorpe et al (1993), who tested cats on a task requiring them to track a moving spot of light using one or the other forepaw. They found that the cats with lateralization of paw preference had a shorter reaction time to commence tracking than those without lateralization of paw preference and concluded that this would be a functional advantage of being lateralized.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, the left eye of chicks with lateralization is consistently faster at detecting a novel stimulus. This result is rather similar to results of Fabre- Thorpe et al (1993), who tested cats on a task requiring them to track a moving spot of light using one or the other forepaw. They found that the cats with lateralization of paw preference had a shorter reaction time to commence tracking than those without lateralization of paw preference and concluded that this would be a functional advantage of being lateralized.…”
Section: Discussionsupporting
confidence: 87%
“…The latter is also in keeping with the superior ability of the human right hemisphere for trajectory perception (Boulinguez et al 2003). Use of the right hemisphere for spatial processing might also explain the use of the left paw by cats to reach for and attempt to grasp small moving targets ( Fabre-Thorpe et al 1993) and the directional bias of the left-hand preference found in squirrel monkeys when they capture live fish, also using a ballistic movement (King & Landau 1993). Fagot & Vauclair (1991) proposed that population biases to use a preferred hand are more common when the task is complex in terms of postural, perceptual and cognitive demands, and some evidence supports this (e.g.…”
Section: Introductionmentioning
confidence: 65%
“…Some studies show no population-level limb preferences (e.g., Poyser, Caldwell, & Cobb, 2006), and others show left (e.g., Fabre-Thorpe, Fagot, Lorincz, Levesque, & Vauclair, 1993) or right (e.g., Gliven, preferences. One study showed right-and left-hand preferences for the same animals (rats) engaged in different tasks (Waters & Denenberg, 1994).…”
Section: Rightward Action Asymmetries In Vertebrates Other Than Marinmentioning
confidence: 99%